2020
DOI: 10.7554/elife.57395
|View full text |Cite
|
Sign up to set email alerts
|

Optical control of ERK and AKT signaling promotes axon regeneration and functional recovery of PNS and CNS in Drosophila

Abstract: Neuroregeneration is a dynamic process synergizing the functional outcomes of multiple signaling circuits. Channelrhodopsin-based optogenetics shows the feasibility of stimulating neural repair but does not pin down specific signaling cascades. Here, we utilized optogenetic systems, optoRaf and optoAKT, to delineate the contribution of the ERK and AKT signaling pathways to neuroregeneration in live Drosophila larvae. We showed that optoRaf or optoAKT activation not only enhanced axon regeneration in both regen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 100 publications
0
24
0
Order By: Relevance
“…A report on axon regeneration after small peptide-induced inhibition of PTPσ indicated that extracellular regulated kinases (Erks) also are involved in regeneration of peripheral axons ( Yao et al, 2019 ). Another group of researchers specifically activated the ERK and Akt signaling pathways and performed a comprehensive study of neural regeneration in both PNS and CNS neurons in live Drosophila ( Wang et al, 2020 ). They found that both ERK and Akt activations enhanced axon regeneration in the sensory neurons in Drosophila larvae ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report on axon regeneration after small peptide-induced inhibition of PTPσ indicated that extracellular regulated kinases (Erks) also are involved in regeneration of peripheral axons ( Yao et al, 2019 ). Another group of researchers specifically activated the ERK and Akt signaling pathways and performed a comprehensive study of neural regeneration in both PNS and CNS neurons in live Drosophila ( Wang et al, 2020 ). They found that both ERK and Akt activations enhanced axon regeneration in the sensory neurons in Drosophila larvae ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another group of researchers specifically activated the ERK and Akt signaling pathways and performed a comprehensive study of neural regeneration in both PNS and CNS neurons in live Drosophila ( Wang et al, 2020 ). They found that both ERK and Akt activations enhanced axon regeneration in the sensory neurons in Drosophila larvae ( Wang et al, 2020 ). These reports strongly suggest that Erk might be involved in the downstream signaling pathway after ChABC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PTEN/AKT pathway was previously implicated to play an important role in theregeneration of both axons and dendrites(Huang et al, 2019, Wang et al, 2020). The territory length and fusion phenomenaat 24h post-dendrotomywasnot affected in akt-1 mutant(Figure3 A-C) suggesting dendrite regeneration in PVD neurons is independent of akt-1 .…”
Section: Resultsmentioning
confidence: 99%
“…OptoRAF but not optoAKT induced neurite outgrowth in PC12 cells and sensory neuron dendrite branching in Drosophila larvae. Activation of optoRAF and optoAKT promoted axon regeneration in the peripheral and central nervous system in Drosophila indicating that these two subcircuits share some downstream components in neuroregeneration [ 74 ].…”
Section: Optogenetic Control Of Receptor Tyrosine Kinase Signalingmentioning
confidence: 99%